Generosity and Effectiveness of Catastrophic Medical Insurance in the People’s Republic of China - ARMIN MÜLLER (Asian Development Review)
In the 2000s, the Government of the People’s Republic of China extended basic health insurance to most of the population. In the 2010s, it introduced a catastrophic medical insurance (CMI) program to further improve urban and rural residents’ protection against financial shocks due to inpatient treatment. This study evaluates the outcomes of CMI. It analyzes a corpus of CMI-related documents to reconstruct the process of policy implementation. Implementation effects were tested using hospitalization data from the China Health and Retirement Longitudinal Study surveys in 2011, 2013, and 2015. The findings indicate that CMI improved reimbursement rates in the basic insurance schemes it complemented. Out-of-pocket payments decreased significantly. However, in prefectural and provincial hospitals, reimbursement rates decreased, most notably due to rising drug spending. This increase may be partly related to the use of higher-quality pharmaceuticals following the introduction of CMI.